Remarks on the (non)existence of word form se (pronoun in accusative case) in the contemporary Czech language - Vesely, Lubos (Bohemica Olomucensia, 2013)
The paper introduces to the problems of description and definition of the word form se in the Czech linguistics, starting from the B. Havranek's view. The author focuses on the syntactic functions of word form se, on the existence of its genitive word form and on the parallels between se and another enclitics in Czech.